Phenomenological Interpretation of Impedance/Capacitance Measurements on Organic Electronic Devices Under Illumination - Santos, L. F. [UNESP]; Pereira, C. J. [UNESP] (Taylor & Francis Ltd, 2014)
The electrical properties of organic electronic devices based on poly(2-methoxy-5-(3',7'-dimethyloctyloxy)-1,-phenylene vinylene) as the active layer were studied under light-excitation at different wavelength ranges and intensities, with particular focus on the frequency-response of the complex capacitance. To interpret the obtained results, an adaptation of abrupt cut-off frequency analysis of the capacitance data was developed considering the displacement of the quasi-Fermi levels due to the incidence of light. The application of such formalism allowed the determination of the position of the bulk Fermi level, the Debye length associated to the photo-generated charge-carriers and the displacement on the quasi-Fermi levels due to illumination.
Keywords: Impedance; capacitance spectroscopy; organic electronic devices; photoconductivity; Conjugated polymers; OLEDs